THE INSURANCE OF LIABILITY AS AN ATTEMPT OF RISK TRANSFERING OVER THE LOSS CAUSED BY NOTARY PULIC AND LAND DEED OFFICIALS - Ghansham Anand; Agus Yudha Hernoko; Mokhamad Khoirul Huda (Yustisia, 2018)
This study primarily aimed to identify the type of insurance of liabilities as an attempt of risk transferring over the loss caused by the notary public and land deed officials. The method of this study was juridical-normative. The result showed that the notary public and land deed officials (PPAT) were both public officials authorized to establish an authentic deed due to clients’ requests. Any violation or negligence by Notary public and land deed officials that was out of the track of legal law might lead the clients into a disadvantageous situation. Such violation or negligence made the established deed null and void, void-able, or even turned into an private deed. This brought an effect to the client as the injured party, and thus, they might file a lawsuit in case of suing for compensation, indemnification, and interest through court proceeding.  Therefore, it needed an agency of risk-transfering in the form of insurance. The insurance of professional liability is a product of public insurance taking-over a risk that is supposed to be charged by the Notary Public and Land Deed Officials. The object of this insurance refers to the insurer’s obligation to pay compensation over particular loss the client has suffered and other expenses due to the risk.